2015
DOI: 10.1136/bcr-2015-210618
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentations and pitfalls of secondary syphilis: osteitis, pneumonia and malignancy

Abstract: SUMMARYSyphilis can show unexpected clinical characteristics rendering its diagnosis difficult. We report on two cases of secondary syphilis presenting with atypical histories of knee or cervical pain and cough. Both had bone involvement and one, pulmonary involvement, documented by MRI, CT scan and PCR. Both responded well to therapy with intravenous aqueous penicillin G followed by intramuscular benzathine penicillin G, but a pulmonary adenocarcinoma was diagnosed during follow-up in one case. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
(4 reference statements)
1
11
0
Order By: Relevance
“…Lung involvement in secondary syphilis was thought to be rare but modern diagnostics such as CT have recently led to a significant increase in reports of secondary pulmonary syphilis 5. In one case series, 60% had symptoms of chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…Lung involvement in secondary syphilis was thought to be rare but modern diagnostics such as CT have recently led to a significant increase in reports of secondary pulmonary syphilis 5. In one case series, 60% had symptoms of chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary syphilis is rare and there are only 14 cases were reported in the English language literature (7). Radiological presentation included infiltrates and solitary or multiple nodules, sometimes associated with pleural effusion and mimicking malignant lesions (8). Diagnosis of osseous or pulmonary syphilis in reported cases was most often made based on radiological images resolving on penicillin in the context of positive serology.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review by David et al 2 in 2006 reported only nine cases of pulmonary syphilis in 37 years ; however, 12 cases were reported in the subsequent eight years. [2][3][4][5][6][7][8][9][10][11][12][13][14] Although a worldwide increase in syphilis incidence was reported in the 2000s, it is still lower than the incidence observed from the 1970s to the 1990s; therefore, the increasing number of cases of pulmonary syphilis is likely not due to the relatively higher syphilis incidence reported recently.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, multiple subpleural nodules were found in all of chest CT scans. [2][3][4][5][6][7][8][9][10][11][12][13][14] reported that no specific lesion could be identified in their literature review. However, recent case reports reveal that multiple subpleural nodules (typically located in the lower lobes) are considered one of the prominent features of pulmonary syphilis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation